Systematic review and practice policy statements on urinary tract infection prevention in adults with spina bifida - Tradewell, Michael; Pariser, Joseph J.; Nimeh, Tony; Elliott, Sean P.; Neurogenic Bladder Research Group, on behalf of the (Translational Andrology and Urology, 2018)
Urinary tract infection (UTI) is a source of morbidity and healthcare costs in adults with spina bifida (ASB). UTI prevention strategies are often recommended, but the evidence of various approaches remains unclear. We performed a systematic review to inform a best practice policy statement for UTI prevention in ASB. On behalf of the Neurogenic Bladder Research Group (NBRG.org), we developed an a priori protocol and searched the published English literature for 30 outcomes questions addressing UTI prevention in ASB. The questions spanned the categories of antibiotics, oral supplements, bladder management factors and social support. Where there was little literature in ASB, we included literature from similar populations with neurogenic bladder (NB). Data was abstracted and then reviewed with recommendations made by consensus of all authors. Level of Evidence (LoE) and Grade of Recommendation (GoR) were according to the Oxford grading system. Of 6,433 articles identified by our search, we included 99 publications. There was sufficient evidence to support use of the following: saline bladder irrigation (LoE 1, GoR B), gentamicin bladder instillation (LoE 3, GoR C), single-use intermittent catheterization (IC) (LoE 2, GoR B), hydrophilic catheters for IC (LoE 2, GoR C), intradetrusor onabotulinumtoxinA injection (LoE 3, GoR C), hyaluronic acid (HA) instillation (LoE 1, GoR B), and care coordination (LoE 3, GoR C). There was sufficient evidence to recommend against use of the following: sterile IC (LoE 1, GoR B), oral antibiotic prophylaxis (LoE 2, GoR B), treatment of asymptomatic bacteriuria (LoE 2, GoR B), cranberry (LoE 2, GoR B), methenamine salts (LoE 1, GoR B), and ascorbic acid (LoE1, GoR B). There was insufficient evidence to make a recommendation for other outcomes. Overall, there are few studies in UTI prevention in the specific population of ASB. Research in populations similar to ASB helps to guide recommendations for UTI prevention in the challenging patient group of ASB. Future studies in UTI prevention specific to ASB are needed and should focus on areas shown to be of benefit in similar populations.